2016
DOI: 10.1111/jfb.13013
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic shifts in fishes between vegetated and unvegetated tidepools: assessing the effect of physical structure on fish habitat selection

Abstract: The aim of this study of tidepool fishes was analyse variation in their use of intertidal habitats (rocky shore, mangrove and salt marsh). Specimens were collected during wet and dry periods from 18 tidepools in the three habitats. A total of 7690 specimens, belonging to 19 families and 30 species, was captured. The fish assemblage in rocky shore pools was clearly distinct from that of vegetated habitats (mangrove and salt marshes). The rocky shore fauna was dominated by permanent resident species, whereas poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…Density was calculated by the number of individuals per pool volume (m 3 ). The fish taxa were assigned to one of three major feeding categories: Carn = carnivore; Omni = omnivore; Herb = herbivore, and the degree of residency was classified according to Macieira and Joyeux (2011), Oliveira et al (2016), complemented by personal observations from the authors.…”
Section: Tidepool Fish Faunamentioning
confidence: 99%
See 1 more Smart Citation
“…Density was calculated by the number of individuals per pool volume (m 3 ). The fish taxa were assigned to one of three major feeding categories: Carn = carnivore; Omni = omnivore; Herb = herbivore, and the degree of residency was classified according to Macieira and Joyeux (2011), Oliveira et al (2016), complemented by personal observations from the authors.…”
Section: Tidepool Fish Faunamentioning
confidence: 99%
“…In northern Brazil, the influence of the Amazon and other estuaries on coastal ecosystems is fundamental to the distribution and organization of marine species (Barletta et al, 2003;Rocha, 2003;Giarrizzo et al, 2010). For example, many of the intertidal ecotones of these two subprovinces are located within estuaries (Giarrizzo and Krumme, 2008;Oliveira et al, 2016), which not only determines the presence of a specific intertidal fish community, but also provides habitats for relatively large populations in comparison with the subprovinces located at higher latitudes (see Supplementary Table S3). Crabtree and Dean (1982) also found that estuarine tidepools harbor high fish densities.…”
Section: Environmental Variables Influencing Intertidal Fish Distribumentioning
confidence: 99%
“…The inter-tidal zone displays an enormous abundance and diversity of organisms despite being the marine ecosystem with the largest and fastest variation in environmental conditions (Little & Kitching, 1996). Its ecological importance is relevant considering the role it plays as feeding, breeding and nursery grounds for many organisms, especially for fishes and crustaceans (Gibson & Yoshiyama, 1999;Horn, Martin, & Chotkowski, 1999;Oliveira et al, 2016). Tropical ecosystems exhibit a wide range of inter-tidal habitats, including both unconsolidated substrates such as mudflats and sandy beaches (Andrades et al, 2014;Oliveira et al, 2016) and hard bottoms as such rocky shores and reef flats (Machado et al, 2015;Macieira & Joyeux, 2011;Macieira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…height and isolation), morphology (e.g. volume, surface area, depth and rugosity), substrate composition and physicochemical conditions (Macieira & Joyeux, 2011;Oliveira et al, 2016). However, factors influencing the organization and structure of tidepool communities remain understudied (Machado et al, 2015;Norton & Cook, 1999) and considerably less understood than those of communities exposed to the atmosphere at low tide (Zander et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation